2012
DOI: 10.1111/j.1443-1661.2012.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index predicts cecal insertion time: The higher, the better

Abstract: A higher BMI is strongly associated with progressively shorter CIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 13 publications
(45 reference statements)
2
21
2
Order By: Relevance
“…While some studies reported a low BMI as a predictor of incomplete or unsuccessful procedures, without taking bowel preparation quality into account [6,20,21], other authors [22,23] demonstrated that an excess BMI ≥25 was significantly associated with worse bowel preparation at colonoscopy, leading to a change in the recommendations after colonoscopy towards an earlier repeat procedure. Accordingly, our data demonstrate that a BMI >25 is an independent predictor of poor bowel preparation at least in the proximal colonic segments, with a 25% higher odds of being inadequately cleaned.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies reported a low BMI as a predictor of incomplete or unsuccessful procedures, without taking bowel preparation quality into account [6,20,21], other authors [22,23] demonstrated that an excess BMI ≥25 was significantly associated with worse bowel preparation at colonoscopy, leading to a change in the recommendations after colonoscopy towards an earlier repeat procedure. Accordingly, our data demonstrate that a BMI >25 is an independent predictor of poor bowel preparation at least in the proximal colonic segments, with a 25% higher odds of being inadequately cleaned.…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged runway time, the type of diet before colonoscopy (liquid or low-fibre), male gender, the use of high volume PEG solutions, non-split dose and excess BMI are considered the main factors associated with inadequate cleansing [5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females are also considered to have less visceral fat, resulting in less tissue supporting the colon than in males thus making endoscope insertion more difficult 16. Older age was associated with longer CIT, as the elasticity of the colon decreases and loops are formed more easily with increasing age 8. Previous studies also found that patients with lower BMI were more difficult to intubate 8,9.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the endoscopic operation technique of the physician, but also patient factors have been reported to affect CS difficulty. Reported CIT-related factors include sex, age, history of abdominal or gynecological surgery, body mass index (BMI), waist circumference, visceral adipose tissue, quality of bowel preparation, and involvement of fellow physicians 812…”
Section: Introductionmentioning
confidence: 99%